Резонансная решетка воздушных пузырьков в магнитодиэлектрической среде - Юрченко, О. Д. (ХНУРЕ, 2021)
The solution and analysis of a problem are considered concerning plane wave scattering by a resonance lattice of spherical air-filled bubbles located in magnetodielectric medium
Keywords: резонансная решетка; магнитодиэлектрическая среда